Denominator Summation Version 2

Algebra Level 3

Find the number of ordered pairs of integers ( a , b ) (a,b) that satisfy this equation:

1 a + b = 1 a + 1 b \dfrac{1}{a+b} = \dfrac{1}{a} + \dfrac{1}{b}


Inspiration

4 4 2 2 1 1 0 0 3 3 \infty

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Hung Woei Neoh
Jun 1, 2016

1 a + b = 1 a + 1 b 1 a + b = a + b a b ( a + b ) 2 = a b a 2 + 2 a b + b 2 a b = 0 a 2 + a b + b 2 = 0 \dfrac{1}{a+b} = \dfrac{1}{a} + \dfrac{1}{b}\\ \dfrac{1}{a+b} = \dfrac{a+b}{ab}\\ (a+b)^2 = ab\\ a^2+2ab+b^2 - ab = 0\\ a^2 + ab + b^2 = 0

Now, we let b b be an integer constant, and a a be the variable. This gives us a quadratic equation. The discriminant,

Δ = b 2 4 ( 1 ) ( b 2 ) = 3 b 2 \Delta =b^2 - 4(1)(b^2) =-3b^2

Since we know that b 2 0 b^2 \geq 0 for all values of b b

b 2 0 3 b 2 0 Δ 0 b^2 \geq 0\\ -3b^2 \leq 0\\ \Delta \leq 0

This implies that for a a to have a real value,

Δ = 0 3 b 2 = 0 b = 0 \Delta = 0 \implies -3b^2 = 0 \implies b=0

However, if b = 0 b=0 , 1 b \dfrac{1}{b} is undefined.

Therefore, no ordered pairs of integers ( a , b ) (a,b) satisfy this equation. The answer is 0 \boxed{0}

Note: There are actually no real values a a and b b that satisfy this equation either

Akash Shukla
Jul 19, 2016

1 a + b = 1 a + 1 b \dfrac{1}{a+b} = \dfrac{1}{a}+\dfrac{1}{b}

a b = ( a + b ) 2 a b 0 \therefore ab=(a+b)^2 \implies ab\geq 0

On solving,

a 2 + b 2 + 2 a b = a b a^2+b^2+2ab=ab a 2 + b 2 = a b a b 0 \therefore a^2+b^2=-ab \implies ab\leq 0

But a b 0 ab\geq 0 . So any one of ( a , b ) (a,b) must be zero which is not possible as inverse of any of two is not possible. So it is not possible. So there exists no such ( a , b ) (a,b)

Krishna Shankar
Jun 26, 2016

Best way is to plot a graph.For the equation. a 2 a b + b 2 = 0 a^2-ab+b^2=0 .

Josh Banister
Jun 1, 2016

Of course a 0 , b 0 a \not = 0, b \not = 0 so consider when they are the same sign. If a , b a,b are both positive then 1 a + 1 b = 1 a + b < 1 a 1 b < 0 \dfrac{1}{a} + \dfrac{1}{b} = \dfrac{1}{a+b} < \dfrac{1}{a} \implies \dfrac{1}{b} < 0 which is a contradiction. If a , b a,b are both negative then ( a , b ) (-a,-b) will also be a solution which as we shown can't happen so if a solution exists, a , b a,b must have opposite signs.

Instead let's look at 1 a b = 1 a 1 b = a b a b \dfrac{1}{a-b} = \dfrac{1}{a} - \dfrac{1}{b} = \dfrac{a-b}{ab} which is the original question with b -b instead of b b such that a , b a,b are both positive. We can't have a = b a=b because a > 0 > b a > 0 > b so we can multiply this equation by a b ( a b ab(a-b to get a b = ( a b ) 2 3 a b = a 2 + b 2 ab = (a-b)^2 \implies 3ab = a^2 + b^2

Now consider a 2 + b 2 0 ( m o d 3 ) a^2 + b^2 \equiv 0 \pmod{3} . By considering the quadratic residue modulo 3. We must have a b 0 ( m o d 3 ) a \equiv b \equiv 0 \pmod 3 . Let a = 3 a , b = 3 b a=3a', b=3b' for some integers a , b a',b' but now this means 1 3 a 3 b = 1 3 a 1 3 b 1 a b = 1 a 1 b \dfrac{1}{3a' - 3b'} = \dfrac{1}{3a'} - \dfrac{1}{3b'} \implies \dfrac{1}{a'-b'} = \dfrac{1}{a'} - \dfrac{1}{b'} and so by Fermats proof by infinite decent, there must exist no solutions to this equation. Again if both a , b a,b are negative then taking the negation would imply a solution where a , b a,b are both positive which is again a contradiction.

Therefore there are no solution to 1 a + b = 1 a + 1 b \dfrac{1}{a+b} = \dfrac{1}{a} + \dfrac{1}{b}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...